2022
DOI: 10.1186/s12890-022-02134-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and changes of physical activity in idiopathic pulmonary fibrosis

Abstract: Background Different clinical predictors of physical activity (PA) have been described in idiopathic pulmonary fibrosis (IPF), but studies are lacking evaluating the potential role of muscle strength and anxiety and depression symptoms in PA limitation. Moreover, little is known about the impact of changes in PA in the course of the disease. The aim of the present study was to investigate the relationship between baseline PA and a wide range of variables in IPF, to assess its longitudinal chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Decreased physical activity was associated with lower progression-free survival (HR 12.1, 95% CI, 1.9–78.8, P = 0.009) in IPF patients. Lower quadriceps strength and higher depression scores contribute to lower physical activity [ 62 ]. Pulmonary rehabilitation using exercise training is effective for improving exercise capacity, dyspnea, and quality of life in IPF patients [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased physical activity was associated with lower progression-free survival (HR 12.1, 95% CI, 1.9–78.8, P = 0.009) in IPF patients. Lower quadriceps strength and higher depression scores contribute to lower physical activity [ 62 ]. Pulmonary rehabilitation using exercise training is effective for improving exercise capacity, dyspnea, and quality of life in IPF patients [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the range of decline in IPF patients to a MCID of 570-1358 steps in our study appears more consistent with the range shown in COPD patients after a medical event. 19 Considering together that physical activity decline is associated with worse survival in COPD and IPF patients, 7,45 judicious evaluation of physical activity may be required to optimize clinical management in IPF patients. Pulmonary rehabilitation and other interventions to promote physical activity may prove advantageous as reflected by an increase step counts per day following these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have investigated longitudinal declines of physical activity in patients with IPF. 7 , 43 Bahmer et al 43 reported that daily step count was declined 3017 steps over 3-years follow-up period in 26 patients. Badenes-Bonet et al 7 observed 784 decline of step count during 12 months in 22 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 261 A higher HADS has been associated with reduced physical activity in people with IPF. 262 There are no studies evaluating the efficacy of anti‐depressant pharmacotherapies specifically in people with ILD, however, they are an important consideration in people with clinical depression, after taking into account drug interactions (e.g., fluvoxamine greatly increases levels of pirfenidone).…”
Section: Non‐pharmacological Therapymentioning
confidence: 99%